1976
DOI: 10.1139/v76-060
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous trifluoroacetic acid as a medium for organic reactions. I. Acidity functions and the identity of the manganese(VII) species found in powerfully acidic media

Abstract: . Can. J. Chem. 54,440 (1976). The HR acidity function has been determined for the trifluoroacetic acid -water system, and extended beyond 100% acid by the addition of trifluoroacetic anhydride, to 99.5 wt.7, anhydride. The existing Ho acidity function is corrected and extended to 1007, trifluoroacetic acid, confirming Eaborn's observation that Ho attains a minimum value at approximately 977, acid.Comparison of the acidity functions shows that although trifluoroacetic acid is only weakly protonating, it is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 13 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The chemical changes that occur as the TFA content of an aqueous TFA solution of potassium permanganate is increased were the subject of a previous paper (7). There we showed that the green species that appears in solutions containing more than 82 Can.…”
Section: Introductionmentioning
confidence: 59%
“…The chemical changes that occur as the TFA content of an aqueous TFA solution of potassium permanganate is increased were the subject of a previous paper (7). There we showed that the green species that appears in solutions containing more than 82 Can.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, N-protonation is borne out [39] but the data may be compatible with some intervention of Oprotonation. Kricheldorf [62] interpreted Dd( 15 N) À 4.6 as Nprotonation, but the acid used (CF 3 COOH, H 0 À 2.7 [63] ) is far too weak to protonate MeSO 2 NH 2 (H 0`À 9 is required). [39] Nitrosamides: The most basic site of Me 2 NNO is predicted to be the oxygen atom in both gas and aqueous phases, by ca.…”
mentioning
confidence: 99%
“…The amount of a loaded nucleoside on solid-support was estimated by the calculation of released 4,4′-dimethoxytrityl cation by a solution of 0.1 M TsOH/CH 3 CN using a molar absorption constant at 498 nm ( ε = 76 000 L mol −1 cm −1 ). 33…”
Section: Methodsmentioning
confidence: 99%